Informal Education for Children of Single Parent Female Workers in Blitar Regency - Hajar, Dewi; Purwito, Lasi; Purnamasari, Ica (Universitas Negeri Malang, 2024)
Informal education is an education obtained from the family environment and its surroundings independently. The family is the first and main place in obtaining education to start life. Every family has its own way in raising children. Social interactions in the family do not just happen, but there are goals to be achieved from all family members. Which causes them to be able to connect and interact with each other, namely the existence of the need that must be met. Connect in the family is inseparable from interaction activities between parents and children. The purpose of this study was to explain the role of the parents of the guardian of the child's informal education of TKWSingle Parentin Blitar Regency. In addition, it also aims to explain the strategy of parents' parents in developing social and emotional children of the TKWSingle Parentin Blitar District. This study uses descriptive research types using qualitative methods. This qualitative research is based on primary data and secondary data. Data collection in this study was conducted with observation and interview techniques. The data obtained were analyzed by the data reduction stages, data presentation and withdrawal of conclusions and verification. Check the validity of this research data is carried out by triangulation of sources and techniques. The results of this study are if informal education from guardian parents is still lacking, then the child will behave arbitrarily and has a negative impact on the child itself. There needs to be more attention and supervision of the parents of the guardian so that informal education of children is specialized about environmental socialization education can develop optimally. Keywords: Informal Education; The Role of Parents of Guardians; Social and Emotional Children